Islamic Enterpreneurship Sebagai Eksistensi Nilai Tambahan Syariah Berbasis Rezeki: Ustman Bin Affan - Rimi Gusliana Mais (ITB AAS INDONESIA Surakarta, 2023)
This research explores thoughts related to economics and entrepreneurship from an Islamic perspective as the existence of sustenance-based sharia added value, taking into account the guidelines of the Koran and facts about Islamic figures. This research method uses literature studies from various article and library sources. Researchers collect and analyze all literary sources that are relevant to the views or thoughts of the Islamic world and Islamic economics of Uthman bin Affan as well as the context of the Islamic world and economics today. The results of research research explain that the Al-Qur'an is a source of Islamic law which has a philosophical basis which is implemented as the objectives of Islamic law determined by Allah SWT to bring goodness to society/humans. With Islamic entrepreneurship and implementation as an existence of added value of sharia based on sustenance for all mankind for success and prosperity. One of the policies implemented by Caliph Uthman bin Affan regarding Islamic economics that is still relevant today is income from commerce